Engineering Ethics - Harris, Jr. Charles E.; Pritchard, Michael S.; Rabins, Michael J.; James, Ray.; Englehardt, Elaine ([S.l.] : Wadsworth Publishing, 2013)
Bridging the gap between theory and practice, ENGINEERING ETHICS, Fifth Edition, will help you quickly understand the importance of your conduct as a professional and how your actions can affect the health, safety, and welfare of the public. ENGINEERING ETHICS, Fifth Edition, provides dozens of diverse engineering cases and a proven and structured method for analyzing them; practical application of the Engineering Code of Ethics; focus on critical moral reasoning as well as effective organizational communication; and in-depth treatment of issues such as sustainability, acceptable risk, whistle-blowing, and globalized standards for engineering. Additionally, a new companion website offers study questions, self-tests, and additional case studies. Available with InfoTrac Student Collections http://gocengage.com/infotrac.
Keywords: Engineering ethics; Globalization